Tsunami Inundation Modelling and Mapping Based on Megathrust Predictions along the Kalianda Coast of Lampung Province Using Delft3D - M Gilang Indra Mardika; Indri Rahmandhani Fitriana; Revin Valent Lumban Tobing (Universitas Sulawesi Barat, 2026)
Indonesia is situated along active subduction zones such as the Sunda Strait, making the country particularly Lampung Province highly vulnerable to megathrust-induced tsunami events. According to data compiled by the National Center for Earthquake Studies 2017, the Sunda Strait has the potential to experience a major earthquake with a magnitude of Mw 8.7–8.8. One notable historical event was the 2018 Kalianda tsunami, which caused numerous fatalities and significant infrastructure damage. This study aims to model and map tsunami inundation in the Kalianda coastal area based on potential megathrust earthquake scenarios. Simulations were carried out using Delft3D and GIS software and validated against historical data from the 2018 tsunami. The validation process used the Mean Absolute Error (MAE) method and correlation coefficient (R), resulting in an error of 0,2357 (23.57%) and a correlation value of 0,543. Three tsunami scenarios were modeled. In Scenario 1, the tsunami wave propagated for 100 minutes, reached a maximum height of 1 meter, and traveled 446,32 meters inland. In Scenario 2, the wave did not reach the shoreline. In Scenario 3, the wave arrived at the coast after 90 minutes, reached a height of 0,4 meters, and inundated up to 1016 meters inland. These results contribute to understanding tsunami hazards and provide insights for improving mitigation strategies in vulnerable coastal areas.